Medical Decisions, Estrogen and Aging - Schulkin, Jay (Springer Netherlands : Imprint: Springer, 2008)
The decision-making process that underlies ovarian hormone therapy (HT) is a fallible one. The question is whether or not physicians should prescribe HT to menopausal women, who are at a time in their lives when they are factoring various concerns into their decision to take (or not take) HT. Not only is it difficult to determine whether or not to prescribe HT, but what kind; should physicians recommend estrogen or progestin, or another combination of related hormones? The decision of whether or not to use HT has affected, and will continue to affect, many women in the United States and throughout the world and is an important model elucidating the forces that influence medical decision-making. Two recent large-scale studies, one conducted here in the United States (the Women's Health Initiative) and the other in Great Britain (the Million Women Study), were highly publicized and cast a negative light on the use of HT. Since HT's inception, views have oscillated, due in part to expectations of benefits extending over the course of long-term use beyond the peri-menopausal period, and perhaps due to the overselling of research investigating the efficacy of HT. Thus, the decision for women to go on HT remains a controversial issue, and the decision-making process is undermined further by overzealous advertising and an exaggerated understanding of the research results (both positive and negative). This book is unique in that it integrates core findings from within the Decision Sciences and Evidence Based Medicine in light of the research that has been done on HT. Medical Decisions, Estrogen and Aging integrates the various components that go into medical decision making in the context of understanding the dilemmas that surround HT. Therefore this book is intended for both specialists and generalists in the field, and it is ideally suited for use by graduate and medical students, medical health care professionals, behavioral scientists, medical ethicists, gerontologists, historians of science, and endocrinologists.